COMPREHENSIVE LITERATURE REVIEW OF MANDUKPARNI (CENTELLA ASIATICA) W.S.R. TO ITS MEDICINAL PROPERTIES - Naveen, Kumar; Suresh, Chaubey; Sanjay Kumar, Singh; Ramesh Chandra, Tewari (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda practitioners have managed and cured physical as well as mental health related disorders when there was no other stream of medicine evolved. The science of Ayurveda has evolved and emerged from ancient times to contemporary era as one of the most significant approach in medicine to treat various diseases. Ayurveda scholars from ancient times have invented and documented various medicinal herbs and their preparation and formulations to be used for the treatment. All Samhita Granths, Chikitsa Granths and Nighantus have quoted many such drugs with their specific uses and indications in particular diseases. Various Nighantus are rich source of knowledge regarding identification, place of origin and indications of various medicinal plants. Later on, with the evolution of technology, more researches were done on the medicinal plants and their utilities in specific disorders were re-evaluated. Mandukparni is one such drug which has been quoted many times in ancient texts as well as in various Nighantus and then more research work was done regarding the medicinal properties of the plants in different ailments. The herb is indicated as Medhya and Rasayana primarily by nearly all Ayurvedic texts including Nighantus. Mandukparni is named Centella asiatica in binomial system of nomenclature. Modern researches have also signified the use of this herb as a potent cognitive drug and having anti-oxidant properties. Alongside, the herb is indicated in many other diseases in ancient and modern texts. This article is an attempt to throw a light on the mentions, formulations and indications of this herb as described in all available texts and research works.